Bimbingan Perkawinan Ditinjau Dari Teori Sadd Adzariah - Hasibuan, Wita Sari Wahyuni; Siregar, Syapar Alim (Jurnal El-Thawalib, 2024)
This study examines the role of marriage guidance in preventing household conflict in the KUA of Padangsidimpuan Utara District in terms of the sadd adzariah theory. The type of research used in this study was field research (Field Research), using a qualitative approach, primary data sources, namely KUA employees in Padang Sidempuan Utara District, bridal couples who conducted marriage guidance at KUA in Padangsidimpuan Utara District, a total of 2 people, the Koran and the fiqh proposal book written by Amir Syarifuddin while the secondary data in this study are books related to sadd adzariah, journals, regulations of the director general of bimas and various other sources. Data collection techniques in this study consisted of interviews, observation and documentation. The data analysis technique in this research is descriptive qualitative. The conclusion of this research is that the implementation of marriage guidance is carried out at the KUA, Padang Sidempuan Utara District, prospective brides who have fulfilled the documents requested by the KUA and have registered to get married will be summoned by the KUA to carry out marriage guidance, the guidance process is carried out routinely every Wednesday and Thursday at 09.00-11.00 guidance is carried out using the lecture method. The material given is about marriage according to Islam, marriage laws, rights and obligations of husband and wife and dealing with problems in the household. Furthermore, marriage counseling held at the KUA of Padangsidimpuan Utara District is one of the efforts to prevent household conflicts after marriage later through material delivered during guidance as well as Sadd Adzariah's theory, namely efforts to inhibit all roads that lead to damage or prevention.